Journalism, Environmental Issues, and Sport Mega-Events: A Study of South Korean Media Coverage of the Mount Gariwang Development for the 2018 PyeongChang Winter Olympic and Paralympic Games. (December 2019) - Yoon, Liv; Wilson, Brian
Few studies on sport and communication consider how environmental issues are reported on—especially in non-Western media. In this article, we report findings from a study of South Korean mainstream and alternative print media coverage of the controversial development of Mount Gariwang for the 2018 PyeongChang Winter Olympic and Paralympic Games. Our study focused on (1) how the decisions and events unfolding around the development of Mount Gariwang were portrayed in South Korean mainstream and alternative news coverage and (2) how the issues at play were politicized and/or depoliticized within and across these outlets. We found that differences in coverage of environmental issues were starkest between, on one side, conservative mainstream media and, on the other side, left-leaning mainstream and alternative media outlets. We also found that environmental controversies were variably politicized or depoliticized in differently positioned media outlets—with left leaning and alternative media highlighting concerns about Olympic-related hypocrisy and corruption, and right-leaning media usually featuring depoliticizing statements from Olympic and government elites. All media outlets highlighted questions about why viable and existing venues were not being used instead of Mount Gariwang, with economic and environmental issues being emphasized differently across outlets. We conclude with reflections on the relevance of our findings for considering links between sport, mediatization, journalism, and environmental politics and suggestions for future research in international coverage of sport- and mega-event-related environmental issues.